A split-brain case study on the hemispheric lateralization of inhibitory control. (May 2017) - D'Alberto, Nicholas; Funnell, Margaret; Potter, Alexandra; Garavan, Hugh
Abstract: Understanding the neurobiological mechanisms underlying inhibitory control is crucial given its role in various disease states and substance abuse/misuse. Neuroimaging research examining inhibitory control has yielded conflicting results on the relative importance of the left and right hemisphere during successful inhibition of a motor response. In the current study, a split-brain patient was examined in order to assess the independent inhibitory capabilities of each hemisphere. The patient's right hemisphere exhibited superior inhibitory ability compared to his left hemisphere on three inhibitory control tasks. Although inferior to the right, the left hemisphere inhibited motor responses on inhibitory trials in all three tasks. The results from this study support the dominance of the right hemisphere in inhibitory control. Highlights: A split-brain patient performed response inhibition tasks with divided visual field. The right hemisphere showed superior inhibitory performance compared to the left. The right hemisphere had faster SSRT on two different Stop Signal Tasks.